Deoxyguanosine is a TLR7 agonist - Davenne, T; Bridgeman, A; Rigby, R; Rehwinkel, J (Wiley, 2019)
Toll-like receptor 7 (TLR7) is an innate immune sensor for single-strand RNA (ssRNA). Recent structural analysis revealed that TLR7 has an additional binding site for nucleosides such as guanosine and is activated when both guanosine and ssRNA bind. The nucleoside binding site also accommodates imidazoquinoline derivatives such as R848, which activates TLR7 in the absence of ssRNA. Here, we report that deoxyguanosine (dG) triggered cytokine production in murine bone marrow derived macrophages and plasmacytoid dendritic cells, as well as in human peripheral blood mononuclear cells, including type I interferons (IFNs) and pro-inflammatory factors such as TNF and IL-6. This signalling activity of dG was dependent on TLR7 and its adaptor MyD88 and did not require amplification via the type I IFN receptor. dG-triggered cytokine production required endosomal maturation but did not depend on the concurrent provision of RNA. We conclude that dG induces an inflammatory response through TLR7 and propose that dG is an RNA-independent TLR7 agonist.